2005
DOI: 10.1002/star.200400356
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Rice Starch-Sucrose Composites

Abstract: The effect of sucrose at different concentrations (0, 10, 20 and 30%) on rheological properties of rice starch pastes (5% w/w) was investigated in steady and dynamic shear. The steady shear properties of rice starch-sucrose composites were determined from rheological parameters for power law and Casson flow models. At 257C all the starch-sucrose composites exhibited a shear-thinning flow behavior (n=0.25-0.44). The presence of sucrose resulted in the decrease in consistency index (K), apparent viscosity (Z a,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
44
0
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 26 publications
10
44
0
7
Order By: Relevance
“…RS alone, like other cereal starches, showed a plateau value of G 0 after a long aging period. A similar trend was reported for other starches, such as corn (Chang, Lim, & Yoo, 2004), rice (Yoo & Yoo, 2005) and sweet potato starch (Lee & Yoo, 2009). In contrast, TS alone showed almost the same G 0 values during aging, showing that TS dispersion at 5 g/100 g concentration produced gels too weak to give a stable G 0 detectable by the instrument.…”
Section: Effect Of Ts Addition On G 0 Of Rsets Blends During Agingsupporting
confidence: 73%
“…RS alone, like other cereal starches, showed a plateau value of G 0 after a long aging period. A similar trend was reported for other starches, such as corn (Chang, Lim, & Yoo, 2004), rice (Yoo & Yoo, 2005) and sweet potato starch (Lee & Yoo, 2009). In contrast, TS alone showed almost the same G 0 values during aging, showing that TS dispersion at 5 g/100 g concentration produced gels too weak to give a stable G 0 detectable by the instrument.…”
Section: Effect Of Ts Addition On G 0 Of Rsets Blends During Agingsupporting
confidence: 73%
“…Chang and others () analyzed rheological properties of the mixtures of corn starch pastes with different carbohydrates and found that their viscoelastic properties decreased in the presence of sugars. Similar conclusions were drawn by Yoo and Yoo () who tested the mixtures of rice starch with sucrose.…”
Section: Introductionsupporting
confidence: 86%
“…The analysis of the effect of changes in sugar type and concentration on viscoelastic properties of paste made from corn starch was based on the results of rheological studies by Chang (Chang and others ) and Yoo (Yoo and Yoo ) for rice starch pastes. The curves of storage G ′ and loss G ″ moduli obtained in the measurements within the angular frequency range from ω = 0.62 to 62 s −1 , it is frequency sweeps over the range of 0.1 to 10 Hz at constant 3% deformation, were described using the power‐law model (Ikeda and Nishinari ) in the following form: G=kωn G=kωnThe values of parameters k ′, k ″ as well as n ′ and n ″ of this model for Chang's measurements are presented in Table and for Yoo's experiments in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to describe the variation in the rheological properties of F and F/T mashed potatoes under steady shear, the data obtained from increasing shear rate measurements were fitted to the well‐known power law () and Casson () models. The Casson model is a structure‐based model that has been used for a number of food dispersions (Rao 1999), including cooked rice flour (Chun and Yoo 2004), acorn flour (Yoo, Kim and Yoo 2005) and rice starch dispersions (Yoo and Yoo 2005). As the development of flow models containing yield stress was not the objective, no additional effort was made on models containing yield stresses (e.g., Hershel–Bulkley).…”
Section: Methodsmentioning
confidence: 99%